2021
DOI: 10.1097/pai.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining for NeuN Does Not Show all Mature and Healthy Neurons in the Human and Pig Brain: Focus on the Hippocampus

Abstract: Neuronal nuclei (NeuN) is a neuron-specific nuclear protein, reported to be stably expressed in most postmitotic neurons of the vertebrate nervous system. Reduced staining has been interpreted by some to indicate loss of cell viability in human studies, while others suggest this may be because of changes in the antigenicity of the target epitope. Preliminary studies in our laboratory found low immunostaining for the NeuN antibody on formalin fixed and paraffin embedded (FFPE) human brain tissue. We report on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In addition, SH-SY5Y cells were examined using neuronal marker labeling. Early neuronal markers include β-III tubulin, a microtubule element, while late neuronal markers include NeuN, a neuron-specific nuclear protein [56,57]. NeuN expression of SH-SY5Y cells in our study showed increase in 2 weeks.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, SH-SY5Y cells were examined using neuronal marker labeling. Early neuronal markers include β-III tubulin, a microtubule element, while late neuronal markers include NeuN, a neuron-specific nuclear protein [56,57]. NeuN expression of SH-SY5Y cells in our study showed increase in 2 weeks.…”
Section: Discussionsupporting
confidence: 45%
“…In our study, approximately 60% of STN neurons are NeuN-ir, which suggests that, in the STN, NeuN labels specific neuronal subpopulation. However, a recent study indicated that in the formalin-fixed, paraffin-embedded (FFPE) human tissue, some NeuN neurons are inadequately stained for quantification purposes ( Luijerink et al, 2021 ). Our samples were formalin-fixed but were not paraffin-embedded.…”
Section: Discussionmentioning
confidence: 99%
“…Nissl body assessment is frequently used in the evaluation of neuronal viability, as the number of Nissl bodies is greatly reduced in damaged neurons [ 29 ]. Furthermore, NeuN is a key neuron-specific nuclear protein that is used as a marker of mature neurons, and the absence of its expression implies attenuated neuronal viability [ 30 , 31 ]. Herein, NTRK1 knockdown resulted in a decrease in the number of Nissl bodies and NeuN-positive neurons in mouse hippocampal tissues.…”
Section: Discussionmentioning
confidence: 99%